Enhancing well-being in hybrid work: the crucial role of organizational support for Indonesia’s State Civil Apparatus - Despinur Dara; Susan Febriantina; Suwatno Suwatno (Cogent Psychology)
This study investigates the impact of Hybrid Working, Perceived Organizational Support, and Job Burnout on Employee Well-being among Indonesian State Civil apparatuses. Using data from 533 respondents selected through simple random sampling, the analysis employed Structural Equation Modeling with a Generalized Least Squares estimation approach. The results reveal that Hybrid Working significantly increases Job Burnout, indicating elevated stress levels from its implementation. Conversely, Perceived Organizational Support reduces Job Burnout and positively influences both Hybrid Working and Employee Well-being. Moreover, Job Burnout negatively affects Employee Well-being, while the positive impact of Hybrid Working on Well-being becomes evident when moderated by Perceived Organizational Support. These findings highlight the critical role of organizational support in mitigating stress and facilitating adaptation to hybrid work systems. The study underscores the importance of designing robust support mechanisms to enhance Employee Well-being and reduce burnout. Practical recommendations are offered for policymakers to develop effective hybrid work strategies tailored to the unique context of Indonesian civil service.